Construction of in vitro 3-D model for lung cancer-cell metastasis study - Jiang, Rongrong; Huang, Jiechun; Sun, Xiaotian; Chu, Xianglin; Wang, Fangrui; Zhou, Jie; Fan, Qihui; Pang, Liewen (BMC cancer, 2022)
Background Cancer metastasis is the main cause of mortality in cancer patients. However, the drugs targeting metastasis processes are still lacking, which is partially due to the short of effective in vitro model for cell invasion studies. The traditional 2-D culture method cannot reveal the interaction between cells and the surrounding extracellular matrix during invasion process, while the animal models usually are too complex to explain mechanisms in detail. Therefore, a precise and efficient 3-D in vitro model is highly desirable for cell invasion studies and drug screening tests. Methods Precise micro-fabrication techniques are developed and integrated with soft hydrogels for constructing of 3-D lung-cancer micro-environment, mimicking the pulmonary gland or alveoli as in vivo . Results A 3-D in vitro model for cancer cell culture and metastasis studies is developed with advanced micro-fabrication technique, combining microfluidic system with soft hydrogel. The constructed microfluidic platform can provide nutrition and bio-chemical factors in a continuous transportation mode and has the potential to form stable chemical gradient for cancer invasion research. Hundreds of micro-chamber arrays are constructed within the collagen gel, ensuring that all surrounding substrates for tumor cells are composed of natural collagen hydrogel, like the in vivo micro-environment. The 3-D in vitro model can also provide a fully transparent platform for the visual observation of the cell morphology, proliferation, invasion, cell-assembly, and even the protein expression by immune-fluorescent tests if needed. The lung-cancer cells A549 and normal lung epithelial cells (HPAEpiCs) have been seeded into the 3-D system. It is found out that cells can normally proliferate in the microwells for a long period. Moreover, although the cancer cells A549 and alveolar epithelial cells HPAEpiCs have the similar morphology on 2-D solid substrate, in the 3-D system the cancer cells A549 distributed sparsely as single round cells on the extracellular matrix (ECM) when they attached to the substrate, while the normal lung epithelial cells can form cell aggregates, like the structure of normal tissue. Importantly, cancer cells cultured in the 3-D in vitro model can exhibit the interaction between cells and extracellular matrix. As shown in the confocal microscope images, the A549 cells present round and isolated morphology without much invasion into ECM, while starting from around Day 5, cells changed their shape to be spindle-like, as in mesenchymal morphology, and then started to destroy the surrounding ECM and invade out of the micro-chambers. Conclusions A 3-D in vitro model is constructed for cancer cell invasion studies, combining the microfluidic system and micro-chamber structures within hydrogel. To show the invasion process of lung cancer cells, the cell morphology, proliferation, and invasion process are all analyzed. The results confirmed that the micro-environment in the 3-D model is vital for revealing the lung cancer cell invasion as in vivo .